Highlights from the Office of the Chief State Law Advisor (International Law) - De Wet, Sandea (South African Yearbook of International Law, 2015)
Writing in 1940 Hans J Morgenthau, whose realist theory saw international politics as a struggle for power, displayed his sceptical view of international law All the schemes and devices by which great humanitarians and shrewd politicians endeavoured to reorganize the relations between states on the basis of law, have not stood the trial of history: Instead of asking whether the devices were adequate to the problems which they were supposed to solve, it was the general attitude of the internationalists to take the appropriateness of the devices for granted and to blame the facts for the failure. At a time when the full horrors of the Second World War were unfolding in Europe and other parts of the world, Morgenthau was of the view that international law was a weak mechanism that could be effective only if pillared upon a system of balance of power.